OXALOSE PRIMÁRIA DIAGNOSTICADA APÓS TRANSPLANTE RENAL - RELATO DE CASO - Almeida, José Bruno de; Costa, Kellen Micheline Alves Henrique; Quinino, Raquel Martins e; Moura, Luiz Antônio Ribeiro de; Félix, Ricardo Humberto de Miranda; Bandeira, Rodrigo de Lima; Silva Júnior, Maurício Ferreira da (Brazilian Journal of Transplantation, 2007)
It is reported a probable case of type 1 primary hyperoxaluria (PH1) in a female young patient whose diagnosis was performed only after the renal transplantation. The purpose of this report is to draw the attention to a rare disease, with hard diagnosis, especially in a patient on substutive renal therapy. The case is related to a 16 years old teenager, on hemodialysis, who was submitted to a living-related donor kidney transplantation (mother), initially presenting a good graft response, with a 1.2mg/dl serum creatinine in the 2nd post-operative day (POD), but developing a progressive and rapid deterioration of the renal function in the 4th POD. A kidney biopsy was performed, and primary oxalosis was diagnosed. Despite the pirydoxine treatment and daily dialysis, the allograft was lost. Definitive treatment of PH1 consists in liver-kidney-transplantation, which must be performed as soon as possible. The knowledgement of such disease among nephrologists is relevant, once patients might be better prepared to renal transplantation, in case the patient is admitted in the ambulatory with this diagnosis.